4x(6x+2)-2(6+x)-20=12x(1+2x)-2x

Simple and best practice solution for 4x(6x+2)-2(6+x)-20=12x(1+2x)-2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x(6x+2)-2(6+x)-20=12x(1+2x)-2x equation:



4x(6x+2)-2(6+x)-20=12x(1+2x)-2x
We move all terms to the left:
4x(6x+2)-2(6+x)-20-(12x(1+2x)-2x)=0
We add all the numbers together, and all the variables
4x(6x+2)-2(x+6)-(12x(2x+1)-2x)-20=0
We multiply parentheses
24x^2+8x-2x-(12x(2x+1)-2x)-12-20=0
We calculate terms in parentheses: -(12x(2x+1)-2x), so:
12x(2x+1)-2x
We add all the numbers together, and all the variables
-2x+12x(2x+1)
We multiply parentheses
24x^2-2x+12x
We add all the numbers together, and all the variables
24x^2+10x
Back to the equation:
-(24x^2+10x)
We add all the numbers together, and all the variables
24x^2+6x-(24x^2+10x)-32=0
We get rid of parentheses
24x^2-24x^2+6x-10x-32=0
We add all the numbers together, and all the variables
-4x-32=0
We move all terms containing x to the left, all other terms to the right
-4x=32
x=32/-4
x=-8

See similar equations:

| 4x(6x+2)-2(6+x)-20=12(1+2x)-2x | | x÷⅔=4/3 | | 4x(6x+2)-2(6+x)-20=12(1+2 | | y^-4+y^-2-42=0 | | 8x-5=5+5 | | (x-1)/(4)=-2 | | p=2/4 | | (x-2)^2=2x^2-1 | | 1,5x+7=13 | | 5½-2⅖=a | | ((4-3x)^1/2)-8=x | | 2b+-5=11 | | 5z-16+6z=0 | | –2j+10j=8j | | 13=2n+5 | | -19=-11+4q | | -7=c/2-9 | | 7p=-10 | | -16(d+1)=-21 | | 31 5÷(z−1 2)=22 3÷(z+1 3) | | n/10+2=27 | | X^-16x+48=0 | | 20=5x+-13+6x | | 14x^2-5x-12=0 | | 4^2x+5=30 | | x/150+x/240=1 | | X²-9x-30=0 | | 3s^2-5s=1 | | 5(3x-2)=7(2x-1x) | | 5(3x–2)=7(2x–1) | | 5+11=g=4 | | 5x-18+8x+3=180 |

Equations solver categories